LIPOSSOMAS CONTENDO ESCINA: ATIVIDADE ANTIBIOFILME IN VITRO EM MATERIAL MÉDICO HOSPITALAR - Dumke, Nádia Márcia (2014)
A great number of nosocomial infections are associated with the use of hospital medical devices, such as urinary catheter, and biofilm formation mainly caused by fungi of the genus Candida. The treatment results in a high cost hospitalization, thereby increasing the permanence of the patient in the hospital environment and increased morbidity and mortality. This is especially harmful in patients with some immune deficiency, such as those caused by old age or with pre-existing medical conditions and also increasing resistance of microorganisms to conventional treatments. In order to investigate new therapies against this microorganism and combine with nanotechnology, studies with the drug escin and liposomes containing this active ingredient have been performed. The characterization of liposomes was carried out, demonstrating a particle size of liposome containing escin to 224 nm and a polydispersity index of 0.288 and liposome without drug, of 354.2 nm and the polydispersity index 0,215. Therefore methods of formation and adherence of biofilm on urinary catheter in vitro using assays for quantification of the biofilm exopolysaccharides and proteins of Candida albicans have been developed. It was subsequently treated with liposomes containing 0.5% escin, liposome without the drug and free drug. The results demonstrated the occurrence of fungal growth inhibition measured at Calcofluor White Stain method and the minimal inhibitory concentration, at a concentration of 1.56 mg/mL for liposome drug containing escin, achieving g a reduction of biofilm by 75% when compared using the free drug. It was observed that the liposome is containing 0.5% escin at a concentration of 1.56 mg/mL, decreased adherence and biofilm formation on medical hospital material, through the techniques used in the study, highlighting the effectiveness of liposome nanostructures against the microorganism C. albicans